Silence in the pre-Islamic and early Islamic eras (Journal of the College of Education for Women, 2025)
Ancient poetry has been the focus of attention of writers and critics, both ancient and modern, as an inexhaustible sea of ​​​​giving and endless pearls. Therefore, it was rich in literary and rhetorical arts. Silence occupied a large space within it, due to its ability to soothe the soul with the fewest words and shortest phrases. Poets resorted to it to express the turmoil in their minds and the worries and pain, or joy and happiness contained within their souls, and because of its potential for complaint and containing feelings Containing feelings, inclining hearts, and sharpening the recipient’s enthusiasm to make him a part of the emotional experience that the poet depicts in his poetry. The research addressed the concept of silence and how it formed a clear feature in the poetry of poets in the pre-Islamic and early Islamic eras, and how they were able to use it to express their various and diverse feelings and emotions through their silence and the use of its techniques of gestures and body language, in addition to the monument that speaks for itself without an intermediary.